Hard Rock and Metal as an Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill examines the differing theoretical frameworks, e.g., subculture and scene, used to examine hard rock and metal fans, arguing that these have worked to the detriment of understanding the gendered experience of music, including taking pleasure in the music. She proposes a new way of thinking about fandom that incorporates fans’ feelings of community. Drawing on Anderson’s (Imagined Communities: Reflections on the Origin and Spread of Nationalism. Verso, 1991) theory of the nation, and feminist writings on community (Weiss and Friedman, Feminism and Community. Temple University Press, 1995), she argues that ‘imaginary community’ better reflects fans’ sense of community, whilst allowing deep consideration of the ideology of the community with particular reference to values, beliefs, traditions and myths. She argues that these are deployed to create a sense of cohesion in spite of inequalities and unacknowledged privileges.
Keywords: Extreme Metal; Gender Construction; Hard Rock; Metal Community; Moral Panic

The Media and the Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter investigates how Kerrang! magazine, a key part of the metal media, creates an imaginary community of hard rock and metal fans. Using semiotic analysis, the author extrapolates four myths that are forged in the letters pages: two that are presented by the magazine as being common sense values of the community (equality and authenticity) and two that are less obvious, the groupie and the warrior, which determine how women and men are portrayed. These myths work together to depict the imaginary community as ideologically invested in maintaining the masculinity of the genre at the expense of femininity. Hill argues that dominant representations of women in the imaginary community render them as adjuncts to the real members of the community—the men—and this has damaging consequences.
Keywords: Hard Rock; Hegemonic Masculinity; Horror Film; Letter Writer; Metal Community